Novel Algorithm to Estimate Fat‐Free Muscle Volumes in Women Using the Urinary Deuterated‐Creatine Dilution Method - Darren Yuen Zhang Tan; Wei Fun Cheong; Shanshan Ji; Amaury Cazenave‐Gassiot; Jane Cauley; Liang Shen; Eu‐Leong Yong (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Muscle mass declines after menopause and is a key risk factor for frailty, falls and poor physical function as women age. The deuterated creatine (D3Cr) dilution method provides a direct assessment of muscle mass, but its accuracy in Asian women has not been evaluated. Our aim was to develop a new D3Cr algorithm incorporating anthropomorphic variables that can estimate fat‐free muscle mass, using magnetic resonance imaging (MRI) as the reference standard. Methods The Integrated Women's Health Programme (IWHP) enrolled 1201 healthy community‐dwelling women, aged 45–69 years at baseline, who attended gynaecological clinics from 2014 to 2016. Between February 2021 and July 2023, 894 participants were recontacted, and 451 of the respondents agreed to ingest 30 mg of D3Cr and had available MRI measurements of fat‐free thigh and erector spinae volumes. Urinary levels of creatine, creatinine and D3‐creatinine levels were measured by tandem mass spectrometry 4 days after ingestion of D3Cr. Muscle mass was estimated using the two D3Cr algorithms (D3Croriginal and D3Crmodified) in current use and a newly developed algorithm (D3CrHt‐Wt) incorporating anthropometric variables that estimate fat‐free muscle volumes. Pearson's correlation analyses were used to compare the performances of the D3Cr algorithms with MRI. Bland–Altman analysis was used to ascertain agreement between D3CrHt‐Wt and MRI. Results Participants (n = 451, mean age 62.6 ± 5.9) were randomly divided into training (n = 367) and validation (n = 84) cohorts. In the training cohort, stepwise multivariable regression modelling indicated that age (β = −0.011, p = 0.076) and ethnicity (β = 0.154, p = 0.317 [Indian]; β = −0.012, p = 0.942 [Malay] compared to Chinese) were not associated with fat‐free muscle volumes. In the final model, D3Cr‐determined creatine pool size (β = 0.032, p < 0.001), body weight (β = 0.030, p < 0.001) and height (β = 4.336, p < 0.001) were independently associated with fat‐free muscle volumes and were incorporated into a new algorithm (D3CrHt‐Wt). In a separate validation cohort, muscle volumes estimated using the D3CrHt‐Wt algorithm (R = 0.813) had a higher correlation with MRI‐measured fat‐free muscle volumes than both D3Croriginal (R = 0.672) and D3Crmodified (R = 0.692) algorithms. Bland–Altman analysis indicated a low bias of 0.112 L and limits of agreement of −0.969 L to +1.190 L. Conclusions Muscle volumes estimated with the D3CrHt‐Wt algorithm had high correlation and agreement with MRI‐measured fat‐free muscle volumes. The convenience of the D3Cr method for participants suggests its potential to be a clinically relevant method for assessing fat‐free muscle volumes in sarcopenia studies.